The Effect of Supportive Educative Nursing Program on Mother’s Knowledge and Attitude of Feeding Practice among Stunting Children Aged 6-24 Months - Lely Suryawati; Harmayetty Harmayetty; Eka Misbahatul Mar'ah Has (Universitas Airlangga, 2020)
Introduction: Supportive educative nursing programs are interventions that can be used to increase family support. The purpose of this study was to analyze the effect of supportive educative nursing programs on the knowledge and attitudes of mothers in feeding stunting children aged 6-24 months.Methods: The research design used was quasi-experimental. The sample used was 54 respondents and divided into two groups: 27 respondents in the treatment group and 27 respondents in the control group by random sampling. The independent variable was the supportive educative nursing program intervention. The dependent variables were knowledge and attitude. The instruments used were the knowledge and attitude of the mother in feeding the stunting toddlers questionnaire—research data obtained by doing pre-test and post-test.Results: There was an effect of the supportive educative nursing program on increasing maternal knowledge in the treatment group (p = 0.000) based on the Wilcoxon test, and there was a significant difference between the treatment group and the control group (p = 0.000) based on the Mann-Whitney test. There was an effect of the supportive educative nursing program on improving maternal attitudes in the treatment group (p = 0.000) based on the Wilcoxon test, and there was a significant difference between the treatment group and the control group (p = 0.000) based on the Mann-Whitney test Conclusion: Intervention of supportive educative nursing programs has a significant influence on increasing the knowledge and attitudes of mothers in feeding stunting toddlers.